Supplement to “Holy matter making holy meaning: fashioning memory, community, and dissimilar similitude in middle Dutch sister-books and The Book of Margery Kempe” - Perk, GG (2022)
This supplement to the MFF article “Holy Matter Making Holy Meaning: Fashioning Memory, Community, and Dissimilar Similitude in Middle Dutch Sister-Books and The Book Of Margery Kempe” surveys comparative research on Margery Kempe and Continental mysticism.